Boosting Indonesia’s Economy Through Hajj and Umrah: Opportunities and Diplomatic Avenues - Mohamad Hery Saripudin; Mansur Juned (Jurnal Hubungan Internasional, 2024)
In the last 50 years, the number of Hajj pilgrims has surged from 200,000 to 3 million. The organization of Hajj and Umrah not only impacts the economy but also serves as a diplomatic tool for both the host country, Saudi Arabia, and the countries of origin of the pilgrims, such as Indonesia. While the economic impact on Saudi Arabia as the destination country has been extensively studied, the effects on the pilgrims’ countries of origin, particularly Indonesia, are less well-documented. Therefore, this paper seeks to explore how Hajj and Umrah, as forms of religious tourism, can generate economic benefits for Indonesia within the Saudi Arabian context. Utilizing a qualitative method, including literature review and observation, this paper explores and elaborates on how Hajj and Umrah can present economic opportunities for Indonesia. The findings suggest that these religious events could benefit Indonesia through various channels: services related to preparation and departure, transportation, export opportunities for Micro, Small, and Medium Enterprises (MSMEs), and as a means of economic diplomacy with Saudi Arabia and other pilgrim-originating countries. There is significant potential to develop these economic opportunities further to enhance Indonesia’s economic diplomacy and directly benefit its people.